How Employee Well-Being and Workload Shape Turnover Intentions Among Retail Employees in Depok City? - Suandi Silalahi; Latif Latif; Rani Sri Sumarsih; Ilma Darojat; Sabrawijaya Sabrawijaya (West Science Social and Humanities Studies, 2026)
Employee mobility has become a growing concern in the retail industry, particularly in urban areas where competitive labor markets encourage frequent job changes. This study aims to analyze the influence of employee well-being and workload on job-hopping intentions among retail employees in Depok City. A quantitative research design was applied using a survey method involving 100 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using SPSS version 25. The results of multiple linear regression analysis show that employee well-being has a negative and significant effect on job-hopping intention, indicating that higher levels of well-being reduce employees’ tendency to change jobs. Meanwhile, workload has a positive and significant effect on job-hopping intention, suggesting that excessive job demands increase employees’ desire to seek alternative employment opportunities. Simultaneously, employee well-being and workload significantly influence job-hopping intention, with a coefficient of determination (R²) of 0.468, meaning that 46.8% of job-hopping intention can be explained by the two variables. These findings highlight the importance of creating supportive work environments and balanced workload management to improve employee retention in the retail sector. The study provides practical implications for retail management in designing human resource strategies that enhance employee well-being and reduce turnover risk.